Atmospheric‐Pressure Plasma‐ and TRAIL‐Induced Apoptosis in TRAIL‐Resistant Colorectal Cancer Cells. Issue 6 (11th February 2015) - Ishaq, Musarat; Han, Zhao Jun; Kumar, Shailesh; Evans, Margaret D. M.; Ostrikov, Kostya (Ken)
<x xml:space="preserve">Abstract</x> The ideal anti‐cancer treatments are those that can selectively kill cancer cells without harming normal cells. Tumor necrosis factor (TNF)‐related apoptosis inducing ligand (TRAIL) is an example of a molecule that can selectively kill cancer cells but not normal cells. However, some tumors are resistant to the TRAIL treatment. We have recently shown that atmospheric cold non‐equilibrium gas plasmas (AGPs) selectively induced cell death in melanoma and colorectal cancer cell lines by activating TNF and caspases 3/7 apoptosis pathways. Here, we demonstrated that AGPs can be used to make TRAIL‐resistant colorectal cancer cells sensitive to the TRAIL treatment. AGPs plus TRAIL promoted the induction of the death receptor 5 (DR5), thereby enhancing the activation and apoptosis of ROS‐dependent caspases 3/7. This study revealed the mechanisms involved in AGP‐assisted TRAIL‐induced cancer cell death and the associated synergistic effects that AGPs has on TRAIL‐resistant colorectal cancer cells.<inline-graphic xlink:href="ark:/27927/pgj11pxf8dr" content-type="ppap201400207-gra-0001" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />